Momentum in professional golf: A fixed effects reassessment of the hot and cold hand fallacy - Ehrlich, J. A.; Paul, R.; Lee, J.; Cain, C. (Journal of Sports Analytics, 2025)
This study investigates the presence and magnitude of hot hand and cold hand effects in professional golf, utilizing PGA Tour data from the 2021-22 through the 2024 seasons. Prior research has yielded mixed results regarding streakiness in golf. To refine these findings, we estimated logistic regression models with fixed effects for both player-seasons and season-tournament-round, controlling for individual ability as well as tournament-specific factors such as course setup and weather. Our results indicate that while a cold hand effect exists and is statistically significant, it is substantially less pronounced than previously reported when additional controls are applied and a larger dataset is used. In contrast, we find minimal evidence supporting a hot hand effect, suggesting that birdie streaks are largely attributable to random variation rather than genuine momentum. Our results align with prospect theory and the principle of loss aversion, implying that golfers may exert greater effort to avoid losses (bogeys) than to pursue gains (birdies). Practically, this insight can inform mental training strategies aimed at promoting consistency and resilience following negative outcomes, thereby mitigating the risk of performance decline across successive holes.